Biological evaluation and in silico studies of novel compounds as potent TAAR1 agonists that could be used in schizophrenia treatment - Wang, Yunjie; Liu, Zhaofeng; Lu, Jing; Wang, Wenyan; Wang, Lin; Yang, Yifei; Wang, Hongbo; Ye, Liang; Zhang, Jianzhao; Tian, Jingwei (Frontiers in Pharmacology, 2023)
Schizophrenia is a complex and severe psychiatric disorder and requires effective treatment with few adverse effects, while trace amine-associated receptor 1 (TAAR1) agonist (SEP-363856) was shown to have promising effects in the preclinical and clinical phases. In this study, we obtained two direct activators of TAAR1, 50A and 50B, by molecular docking and molecular dynamics (MD) simulation screening. Compound 50B with higher TAAR1 agonistic activity was shown to have no agonistic effect on dopamine D2 receptors and exhibited superior inhibition of MK801-induced hyperactivity in mice. What is more surprising is that 50B had the excellent druggability, the ability to penetrate the blood-brain barrier and did not cause adverse EPS reactions in mice, such as catalepsy. Take together, the above results fully demonstrated the beneficial role of TAAR1 agonist activity in the treatment of schizophrenia, and the discovery of a structurally novel TAAR1 direct activator (50B) that may be of assistance for the treatment of schizophrenia.